Pengembangan Bahan Ajar Membaca Braille Pada Siswa Tunanetra Kelas II di SLB-A YAPTI Makassar - Anisah, Nur; Syamsuddin, Syamsuddin; Hadis, Abdul (-, 2025)
This study investigates the issue concerning the availability of Braille reading instructional materials for students with visual impairments, which poses a challenge for teachers in delivering effective Braille reading instruction. The aim of this research is to identify the level of need for instructional materials in Braille reading for visually impaired students, the stages of instructional material development, as well as the validity and practicality levels of the developed materials. This study employs research and development (R&D) methodology using the 4D development model (Define, Design, Develop, and Disseminate). Data were collected through interviews, observations, and questionnaires. The data analysis techniques involved collecting data, scoring, assigning weights, and calculating percentages. The instruments used in this study include validation instruments to assess the validity of the instructional materials and trial instruments using a Likert scale questionnaire to evaluate the feasibility of the materials. The results of the prototype product development indicate that the instructional materials can be utilized in Braille reading instruction for students with visual impairments. This is supported by validation results, which fall into the valid category and qualify for trial implementation. The product trials conducted with teachers and students demonstrate that the materials are applicable in Braille learning, especially for students at the elementary level.